Sleep Disorders in Leucine-Rich Glioma-Inactivated Protein 1 and Contactin Protein-Like 2 Antibody-Associated Diseases - Lin, Nan; Hao, Honglin; Guan, Hongzhi; Sun, Heyang; Liu, Qing; Lu, Qiang; Jin, Liri; Ren, Haitao; Huang, Yan (Frontiers in Neurology, 2020)
Objective. Sleep disorders are common in voltage-gated potassium channel complex antibody (VGKC-Ab)-associated diseases. The aim was to investigate the sleep disturbances and polysomnography (PSG) characteristics in patients with VGKC-Ab- associated diseases. Methods. Twenty-seven patients with leucine-rich glioma-inactivated protein 1 antibody (LGI1-Ab) encephalitis, 7 patients with contactin-associated protein-like 2 antibody (Caspr2-Ab) associated diseases, and 14 healthy controls with at least one PSG or actigraphy recording were recruited at Peking Union Medical College hospital from January 2014 to July 2019. Results. Sleep disorders including insomnia, hypersomnia, REM sleep behavior disorder (RBD), periodic limb movements in sleep (PLMS), agrypnia excitata, and obstructive sleep apnea syndrome were observed. Twenty-one PSG recordings from patients with LGI1-Ab encephalitis demonstrated a decrease in total sleep time (TST) (median 365.5, range 184.5-495.5 min), sleep efficiency (70.0%, 47-92%), N3 sleep (9.7%, 0-32.9%), and REM sleep (9.9%, 0.4%-27.9%). Of 5 patients with Casrp2-Ab associated diseases, TST was found to be 329.5 (167.0-377.5 min) and sleep efficiency was found to be 61.7% (34.6-71.7%). The percentage for N3 and REM sleep was found to be 15.0% (0-34.6%) and 12.7% (0-22.2%), respectively. Both RBD and PLMS were observed more frequently in patients with LGI1-Ab encephalitis. We identified status dissociates (SD) in 5 (23.8%) patients with LGI1-Ab encephalitis and 2 (40%) patients with Caspr2-Ab-associated diseases. The former was more likely to have simple limb movements rather than complex movements which mimick the contents of their dreams. Continuous insomnia was more common in patients with Caspr2-Ab-associated diseases than patients with LGI1-Ab encephalitis. Patients reported clinical and PSG improvements following immunotherapy. Conclusion. Sleep disorders in patients with VGKC-Ab associated diseases include decreased TST and poor sleep efficiency. Our studies provide evidence of SD in patients with LGI1-Ab encephalitis.